Self and Group Initiated Professional Development Pursuits of EFL Teachers - Nana Priajana (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT Teachers’ quality plays a paramount role in the improvement of education quality. One of the ways to ensure high quality teachers is through effective continuous professional development for teachers. This present study is aimed to explore how EFL teachers develop their professionalism, particularly in terms of pedagogical and professional competencies. This research involved seven outstanding English teachers teaching at junior and senior high schools from two different areas covering one municipality and a district in Cirebon. The result showed that there are two main themes of professional development pursuits of the outstanding teachers comprising of self-initiated or individual and group professional development activities. ABSTRAK Kualitas guru berperan penting dalam menjaga kualitas pendidikan. Salah satu cara memastikan guru untuk tetap berkualitas adalah melalui aktivitas pengembangan profesionalisme yang efektif bagi guru. Penelitian ini bertujuan untuk mengeksplorasi bagaimana aktivitas guru bahasa Inggris mengembangkan profesionalisme mereka terutama dalam hal kompetensi pedagogis dan profesional. Penelitian ini melibatkan tujuh guru bahasa Inggris luar biasa yang mengajar di tingkat SMP dan SMA dari dua wilayah yang berbeda yang mencakup satu kotamadya dan sebuah kabupaten di Cirebon. Hasil penelitiannya menunjukkan bahwa ada dua pola utama aktivitas pengembangan profesional dari guru bahasa Inggris yang terdiri dari kelompok sendiri / individu, dan kelompok. Penelitian ini menyimpulkan bahwa guru bahasa Inggris dapat melakukan kegiatan profesinya yang diinisiasi sendiri dan kelompok untuk mempertahankan profesionalisme mereka sebagai guru. How to Cite: Priajana, N. (2017). Self and Group Initiated Professional Development Pursuits of EFL Teachers. IJEE (Indonesian Journal of English Education), 4(1), 31-48 doi:10.15408/ijee.v4i1.6597.